Determinación de la concentración de mercurio en atún enlatado y valoración clínica de consumidores de las tres marcas de mayor demanda que se expenden en los principales centros de abastecimiento de la ciudad de Machala desde octubre del 2007 a julio 2008. - Díaz Calderón, Yolanda M. (2008)
The mercury is a broadly chemical compound utilized from the antiquity for diverse ends. AT the moment it is used in the industry, mining, the iron and steel industry, and the production of chlorine. Most of the mercury liberated by the human activity, is thrown to the air, through it burns of fossil products, foundries and combustion of solid residuals the contamination of the soil and the water is give with the application of fertilizers in the agriculture and pour of industrial waste waters.